Evaluasi non-destruktif pada pemalsuan tepung kacang merah (Phaseolus vulgaris L.) menggunakan spektroskopi visible-near infrared (VIS-NIR) - Laila Rahmawati; Hari Hariadi (AGROINTEK, 2023)
Food adulteration is one of the biggest concerns of quality control. Food adulteration is adding or replacing a product with one or more similar products to increase economic value. Unwanted food adulteration in bean flour was mixing beans with other flour. This study aimed to determine the adulteration of red kidney bean flour using Vis-NIR spectroscopy of 350-1000 nm. The sample was red kindey beans flour adulterated with red rice flour, wheat flour, and white rice flour at 10%, 20%, 30%, 40%, and 50%.  Principal component analysis (PCA) and Partial Least Square Regression (PLSR) were used based on spectra pre-processing technique (Savitsky-Golay 1st and 2nd derivative, multiple scatter correction (MSC), and standard normal variates (SNV). SNV method gave the best calibration and model on white rice flour as an adulterant in Rc2 (0.99), RMSEC (1.23), Rv2 (0.77), RMSEV (7.79), Rp2 (0.99) and RMSEP (1.25). Otherwise, the PLSR analysis in red rice flour and wheat flour as adulterant gave the raw spectra for the model's best result.  The obtained Vis-NIR models demonstrated the technology novelty in evaluating red kidney bean flour.